A WHITE PALETTE GATHERING: A LITERATURE SYNTHESIS IN ONE ACT - McGarry, Karen (Art/Research International)

(untitled) (University of Alberta, 2021)
Storytelling, a tenet of Critical Race Theory, offers a distinct approach for researchers engaging in narrative inquiry. This article models a fiction as research approach for creating a literature synthesis as a pedagogical strategy for teacher educators and pre-service teachers. The white palette refers to a painting palette, a blank slate or canvas, often considered neutral ground. Whiteness, however, is not neutral and this one-act conversation centers on examining whiteness as it impacts my role as a white teacher educator. The production, players, and script developed out of salient literature inclusive of Critical Race Theory, Art Education, and Critical Whiteness Studies. I am both author and a participant in this story. In this capacity, I disclose the impacts of the literature on my white teacher educator identity and reveal how I created arts-based data artifacts to evidence the overall story.